2020
DOI: 10.1186/s13550-020-00707-0
|View full text |Cite
|
Sign up to set email alerts
|

KRAS mutation effects on the 2-[18F]FDG PET uptake of colorectal adenocarcinoma metastases in the liver

Abstract: Background Deriving individual tumor genomic characteristics from patient imaging analysis is desirable. We explore the predictive value of 2-[18F]FDG uptake with regard to the KRAS mutational status of colorectal adenocarcinoma liver metastases (CLM). Methods 2-[18F]FDG PET/CT images, surgical pathology and molecular diagnostic reports of 37 patients who underwent PET/CT-guided biopsy of CLM were reviewed under an IRB-approved retrospective research protocol. Sixty CLM in 39 interventional PET scans of the 3… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…For patients who are candidates for image-guided therapy, such as ablation or radioembolization, fusion pre-acquired PET-CT images can be fusion with a real-time ultrasound ( 42 ) or in a follow-up after radiofrequency ablation (RFA), since PET/CT is superior to CT for demonstrating recurrence after RFA in about 25% of the patients, mainly the patients with multiple and bilobar lesions ( 43 ). Moreover, a previous study has found a correlation in KRAS mutations with 2-[18F]FDG uptake in PET images ( 44 ).…”
Section: Pre-operative Stagingmentioning
confidence: 88%
“…For patients who are candidates for image-guided therapy, such as ablation or radioembolization, fusion pre-acquired PET-CT images can be fusion with a real-time ultrasound ( 42 ) or in a follow-up after radiofrequency ablation (RFA), since PET/CT is superior to CT for demonstrating recurrence after RFA in about 25% of the patients, mainly the patients with multiple and bilobar lesions ( 43 ). Moreover, a previous study has found a correlation in KRAS mutations with 2-[18F]FDG uptake in PET images ( 44 ).…”
Section: Pre-operative Stagingmentioning
confidence: 88%
“…While PET/CT imaging plays a pivotal role in cancer detection and management, its accuracy can be influenced by serum enzyme levels. Researchers have even explored the predictive value of 2-[18F]FDG uptake in colorectal adenocarcinoma liver metastases (CLM) with regard to the KRAS mutational status [ 23 ]. The relationship between serum liver enzyme levels (SGOT/SGPT) and the liver's standard uptake values (SUV) on FDG-PET is complex and can be influenced by various factors related to liver function, disease, drug effects, metabolic status, and even the genetic makeup of an individual.…”
Section: Discussionmentioning
confidence: 99%